2000
DOI: 10.1590/s0066-782x2000001100006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the risk factors for allograft vasculopathy in asymptomatic patients after cardiac transplantation

Abstract: Objective -To study the influence of immune and nonimmune risk factors on the development of allograft vasculopathy after cardiac transplantation. Methods - (24.53±4.3 versus 28.11±4.6; p=0.019). studied. Conclusion -Body mass index was an important marker of allograft vasculopathy in the population

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
9
0
4
Order By: Relevance
“…In a previous study, we also documented the influence of this factor in the development of CAV. 4 Body mass index may be much more than an anthropometric index and may reflect a metabolic disorder that occurs in some patients after heart transplantation. Insulin resistance is a marker of cardiovascular events in the atherosclerotic process, but this concept is not well established in heart transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we also documented the influence of this factor in the development of CAV. 4 Body mass index may be much more than an anthropometric index and may reflect a metabolic disorder that occurs in some patients after heart transplantation. Insulin resistance is a marker of cardiovascular events in the atherosclerotic process, but this concept is not well established in heart transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported that up to 10% of patients in the 1st year and up to 50% of patients in the 5th year of follow-up after heart transplantation have evidence of CAV in coronary arteriograms. 4 Clinically, this disease is insidious and usually gives no clues until heart failure, myocardial infarction, or death occurs. [5][6][7][8] Nevertheless, routine evaluation with coronary angiography, thrombolysis in myocardial infarction frame counts, and intravascular ultrasound is undesirable because these tests are invasive, expensive, not without risk, and sometimes inaccurate.…”
mentioning
confidence: 99%
“…However, it seems to be low, less than 10% of the patients undergoing CT 280,297,320 . For the purpose of diagnosis and prevention, the same methods used for other etiologies are recommended [321][322][323][324] .…”
Section: Graft Coronary Artery Diseasementioning
confidence: 99%
“…Despite achieving significant strides in short term survival, the challenges of long-term survival remain unresolved. Chronic rejection, cardiac allograft vasculopathy (CAV), malignancy and renal insufficiency hinder the long-term survival and are direct contributors to graft dysfunction and graft failure [1][2][3][4][5]. CAV remains one of the major causes of mortality and morbidity following the first year of cardiac transplantation [1,2].…”
Section: Introductionmentioning
confidence: 99%